Organic syntheses based on name reactions - Hassner, Alfred, 1930- (Pergamon, 2002)
Organic Syntheses Based on Name Reactions.
"First edition 2002"--Title page verso
Revised edition of: Organic syntheses based on name reactions and unnamed reactions. 1st ed. 1994.
Includes indexes.
Keywords: Organic compounds -- Synthesis.; elektronické knihy; electronic books